Population biology of the livestock-toxic species Phalaris angusta Nees ex Trin. (Semiárida, 2023)
The native species Phalaris angusta (alpistillo) is present in the ecosystems of the Argentina central semi-arid region. The objective of this work was to evaluate some demographic aspects as germination and seed bank. The work was carried out at the Pichi-Carhué Establishment, in La Pampa center-east. In a closure, two cohorts were followed up from July to December 2019, one located in a sunny area and the other in a shaded area. Vegetative and reproductive attributes were evaluated. In addition, the total and germinable seed bank was determined at two moments (pre and post-dissemination). Finally, the germination of harvested seeds was evaluated. There were differences in the survival curves for both cohorts. The fecundity indicators: number of panicles/flowers/seeds per plant were higher for the sun exposed cohort. The shaded areas favored the vegetative stages of the alpistillo, while the sunny ones the reproductive ones. The seed bank was always greater for the sunny areas. The germination of the seed bank presented a viability of 45% and a germination percentage close to 55 %.
Keywords: cattle toxicity; germination; narrow canarygrass; plant demography; seed bank